THE IMPACT OF INTERNATIONAL TRADE WARS ON THE ECONOMIC STABILITY OF DEVELOPING COUNTRIES - Anggia Faradina (Nomico, 2024)
This study aims to analyze the effect of international trade wars on the economic stability of developing countries by focusing on three main indicators, namely Gross Domestic Product (GDP), exports, and unemployment rates, the trade war between the United States and China since 2018 has created significant global pressure on the structure of international trade and has greatly impacted developing countries that have a high dependence on foreign trade, this study uses an associative quantitative approach with time-series data for the period 2019–2023 collected from various international sources such as the World Bank, IMF, and Global Trade Alert, the analysis technique used is multiple linear regression through EViews 12 software, with classical assumption tests to ensure validity. The results of the study show that the trade war intensity variable has a negative and significant effect on economic stability, while exports have a significant positive effect and an increase in the unemployment rate has a negative effect on economic stability, simultaneously, the three independent variables explain 78.2% of the variation in the economic stability of developing countries, which indicates that the impact of trade conflicts is very real structurally and macroeconomically.